Spanish seamen (circular) - Tewson, Vincent
C01-0010-001 Telegraphic Address: TRADUNIC, SOWEST, LONDON. Telephone: VICTORIA 9020 TRADES UNION CONGRESS GENERAL SECRETARY SIR WALTER CITRINE, K.B.E. TO WHOM ALL COMMUNICATIONS SHOULD BE ADDRESSED. TRANSPORT HOUSE, SMITH SQUARE, LONDON, S.W.1. Department International Our Ref. HVT/AEC/MS/159 Your Ref. 21st December, 1939. TO SECRETARIES OF CERTAIN TRADES COUNCILS. In reply please quote:- CIRCULAR NO. 41 (1939-40) Dear Sir (Madam), SPANISH SEAMEN. With reference to our letter of 5th December, 1939, on the subject of facilities for the employment of the Spanish seamen in our charge in this country, we have now secured, through the good offices of the Basque Delegation, particulars of the technical qualifications of the men in your locality. I am enclosing a list for your information, as I thought it might be helpful in any opportunities for work which may arise. The particulars may also enable you to make contact with the local or full-time District Secretary of the Unions catering for the workers in the various classes of employments shown on the list. If this consultation took place, you would be able to ascertain the state of the labour market locally, and, if circumstances were favourable, solicit the interest and support of Union officials in placing the men in jobs where British labour would not be displaced, and where Trade Union rates of wages and conditions would not be undermined. I am fully appreciative that this is not an easy task to follow up, but probably with the good-will and assistance of other members of your Council, some progress may be made to enable advantage to be taken of any cases where employment might be available, and in which the Unions themselves might be prepared to help. Wishing you the Compliments of the Season, Yours sincerely, H.V. TEWSON, Assistant Secretary. 292C/946/1/10